The Internet and its protocols a comparative approach - Farrel, Adrian (Amsterdam ; Boston : Morgan Kaufmann Publishers, 2004)
The view presented in The Internet and Its Protocols is at once broad and deep. It covers all the common protocols and how they combine to create the Internet in its totality. More importantly, it describes each one completely, examining the requirements it addresses and the exact means by which it does its job. These descriptions include message flows, full message formats, and message exchanges for normal and error operation. They are supported by numerous diagrams and tables. This book's comparative approach gives you something more valuable: insight into the decisions you face as you build and maintain your network, network device, or network application. Author Adrian Farrels experience and advice will dramatically smooth your path as you work to offer improved performance and a wider range of services. * Provides comprehensive, in-depth, and comparative coverage of the Internet Protocol (both IPv4 and IPv6) and its many related technologies. * Written for developers, operators, and managers, and designed to be used as both an overview and a reference. * Discusses major concepts in traffic engineering, providing detailed looks at MPLS and GMPLS and how they control both IP and non-IP traffic. * Covers protocols for governing routing and transport, and for managing switches, components, and the network as a whole, along with higher-level application protocols. * Offers thoughtful guidance on choosing between protocols, selecting features within a protocol, and other service- and performance-related decisions.
Ch 1 Overview of Essentials Ch 2 The Internet Protocol Ch 3 Multicast Ch 4 Routing Ch 5 Concepts in IP Security Ch 6 IP Service Management Ch 7 Transport Over IP Ch 8 Traffic Engineering Ch 9 MPLS (Multiprotocol Label Switching) Ch 10 Generalized MPLS Ch 11 Managing Switches and Components Ch 12 Network Management Ch 13 Application Protocols Ch 14 Advanced Applications Ch 15 Future Developments.
Includes bibliographical references and index.
Keywords: Computer network protocols; Internet; Electronic books